Exploring the Trajectory and Prevention of Alcohol Use Among Young People From the Perspective of Professional Youth Workers. Issue 2 (April 2019) - Haglund, Kristin; Hayter, Mark
Abstract : Abstract: Excessive alcohol use is a significant health issue. Underage drinking is one expression of excessive alcohol use. Researchers have identified a trajectory of alcohol involvement. Gaps exist in understanding the influences that delay and promote the trajectory of alcohol use among young people. The purpose of this study was to explore the contexts and influences that limited and contributed to the trajectory of alcohol use among young people. A qualitative descriptive design was used. Eight youth workers from a city in Northern England participated in individual audio-recorded semistructured interviews. Transcriptions were coded. Data were analyzed within, and across, codes to identify themes. The theme "Alcohol is an Expected Part of Life" characterized a hypothetical trajectory of alcohol involvement. "Fostering Community in Youth Centers" characterized how participants' perceptions informed their work. The results increase understanding of how contexts may influence initiation, promotion, and prevention of alcohol use among young people.